Beneficence-Based Obligations and Ethics Consultation in Assisted Dying - Marckmann, Georg (Bioethics, 2026)
In ethical debates on assisted dying, the principle of respect for autonomy is usually invoked to justify respecting requests for assisted dying. However, there are not only autonomy-based obligations, but also obligations arising from the principle of beneficence towards persons requesting assisted dying. What beneficence requires from persons providing assistance in dying is, however, far less obvious. We will argue that obligations of beneficence, in contrast to autonomy-based obligations, cannot fulfil a gatekeeping function in regulating access to assisted dying, that is, differentiate between ethically justified and unjustified cases. Nevertheless, they can and should play an important role in this context: Based on philosophical considerations on the concept of well-being, which is the focus of the principle of beneficence, we elaborate three different roles of beneficence-based obligations in the context of assisted dying: providing high standards of care, supporting autonomous decision-making and offering ethical guidance for health care professionals who consider providing assistance in dying. As we will show, these beneficence-based obligations can also support ethics consultation in assisted dying, especially in cases where there is ethical uncertainty among the assisting persons about whether they should follow the request and provide assistance in dying. Based on a principle-based approach to integrated ethical decision-making, we will demonstrate how an elaborated understanding of well-being and the specified beneficence-based obligations can contribute to balancing competing ethical obligations and promote ethically sound decisions in requests for assisted dying. The suggested approach can be used as a guidance for ethics consultation in requests for assisted dying.